Die Wiedergutmachung immaterieller Schäden im Privatrecht - Schubert, Claudia (Mohr Siebeck, 2013)
Claudia Schubert provides a comprehensive analysis of the compensation for non-economic damages in private law. She redefines the concept of non-economic damages, combines the individual sections in this concept, makes a proposal for a selective increase in the compensation for non-pecuniary damages and advocates an independent regulation of civil sanctions for the extension of the law of damages.
PublicationDate: 20130416
Keywords: Privatrecht -- Rechtsvergleichung -- Arbeitsrecht -- Europarecht -- Völkerrecht -- Bürgerliches Recht -- Internationales Privatrecht -- Arbeits- und Sozialrecht